Konseling Karir Di Sekolah Dan Dunia Kerja Dalam Perspektif Pendidikan Islam - Kurnia, Asraf; Suhaili, Hidayati; Kenedi, Gusril; Ihsan, Sartika Fortuna (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This literature review aims to identify and analyze the significant role of career counseling in schools to prepare students for the dynamic workforce, especially within the context of Islamic education. In an era of globalization and rapid technological advancement, school-based career guidance plays a crucial role in helping students understand their potential and explore available career options. This study reviews the concept of work in Islam, career preparation at different educational levels, career counseling theories, career planning, decision-making, career development, and relevant supporting activities. The approach integrates Islamic ethical and spiritual values as a foundation for career decision-making. The findings indicate that career counseling based on Islamic values can guide students to achieve not only professional success but also contribute positively to society. Therefore, a comprehensive and continuous approach in career counseling can shape individuals who possess good character and are ready to face changes in the job market.